2013
DOI: 10.1371/journal.pone.0065945
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epigenetic Factors in Mouse Embryonic Neural Stem Cells Exposed to Hyperglycemia

Abstract: BackgroundMaternal diabetes alters gene expression leading to neural tube defects (NTDs) in the developing brain. The mechanistic pathways that deregulate the gene expression remain unknown. It is hypothesized that exposure of neural stem cells (NSCs) to high glucose/hyperglycemia results in activation of epigenetic mechanisms which alter gene expression and cell fate during brain development.Methods and FindingsNSCs were isolated from normal pregnancy and streptozotocin induced-diabetic pregnancy and cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…Neurogenesis and neural migration are affected by these changes. 59 Hyperglycemia also induces reactive oxygen species (ROS) production and intracellular oxidative stress in NSCs, altering the balance between their proliferation and apoptosis. 60 Reduction of ROS is, therefore, one strategy to overcome NSC dysfunction during fetal development in the presence of high glucose.…”
Section: Hyperglycemic Impairments In Nscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurogenesis and neural migration are affected by these changes. 59 Hyperglycemia also induces reactive oxygen species (ROS) production and intracellular oxidative stress in NSCs, altering the balance between their proliferation and apoptosis. 60 Reduction of ROS is, therefore, one strategy to overcome NSC dysfunction during fetal development in the presence of high glucose.…”
Section: Hyperglycemic Impairments In Nscsmentioning
confidence: 99%
“…Murine studies show that once the blastocyst has been exposed to hyperglycemia, exertion of tight glycemic control is insufficient to prevent or reverse congenital defects that have already occurred. 59 Given the impairments within progenitor cells during diabetes, the impact of hyperglycemic reversal on cell functionality is crucially important for designing targeted therapeutics. Specifically, if cells display hyperglycemic memory suggestive of permanent modifications that are passed to daughter cells, the translational potential for autologous therapies may be limited.…”
Section: Diabetic Stem and Progenitor Cell Defects Are Reversible Onlmentioning
confidence: 99%
“…In mice, many C2MC miRNAs were identified to be the major components in the dynamic regulatory network during embryonic development [39], skeletal and cardiac muscle differentiation or function [9,36], angiogenesis [3] and lung development [37]. Studies have also shown that many C2MC miRNAs or their relatives were often among the most significantly-altered miRNAs in responses to multiple types of cellular stresses, which included nutrition deprivation [11], hyperglycemia [3,38], hypertonic stress [16], oxidative stress [43], xenobiotic stress [41], aging [48], cigarette smoke [17,18], septic shock [40] and virus infection [7,28]. Although there were studies showing that a few C2MC miRNAs might act as important ribo-regulators in the control of cell fate decision, cell proliferation, immune responses, cell cycle and apoptosis [9,11,27,32,37,39,49], the exact roles of many more C2MC miRNAs in cellular stress responses and other biological processes were unknown and remained to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Spruce et al suggested that miR-297b-3p, miR-466a-3p, miR-467-5p/3p and miR- 669a-3p, which are highly enriched in both embryonic and extraembryonic cells, co-target cyclin-dependent kinase inhibitor 1C (Cdkn1c or p57) and RAS p21 protein activator 2 (Rasa2) to participate in the regulation of differentiation and early development [39]. Similarly, in neural stem cells, high glucose/hyperglycemia caused significantly reduced expression of miR-200a-3p, miR-200b-3p, miR-466a-3p, miR466d-3p, which were demonstrated to co-target Doublecortin (Dcx) and Platelet activating factor acetyl hydrolase, isoform 1b, subunit 1 (Pafah1b1), two genes involved in neurogenesis [38]. The later study is of special interests also in that miR-200a-3p, miR-200b-3p, miR-466a-3p and miR-466d-3p are very significantly down-regulated together under hyperglycemia, which lends further support to the notion that under certain circumstances miR-466(a/b/c/e/p) and miR-200b-3p can be regulated in the same direction in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia alters the epigenetic mechanisms in neural stem cells, resulting in altered expression of some development control genes, which may form the basis for some neural tube defects. Since epigenetic changes are reversible, once can argue their value as therapeutic targets in order to improve fetal outcomes in diabetic pregnancy (Shyamasundar et al 2013 ).…”
Section: High Fat Intake and Gdmmentioning
confidence: 99%